Annie Jordan : a novel of Seattle - Post, Mary Brinker, 1906-1966 (Doubleday, 1948)
Annie Jordan was a wild and untamed as the great Northwest at the turn of the century, and her rise to wealth and position paralleled the growth of Seattle.